2016
DOI: 10.1186/s13005-015-0096-3
|View full text |Cite
|
Sign up to set email alerts
|

Orbital floor fractures – short- and intermediate-term complications depending on treatment procedures

Abstract: BackgroundMany reconstruction materials for orbital floor fractures have been described in the past including autologous bone transplants, resorbable polymers and titan meshes. So far evidence is missing which material is used successfully regarding indication and particular size of defect. Therefore the aim of this study was to evaluate which reconstruction technique produces best clinical outcome and least complications associated with indication.MethodsRetrospectively, surgical and ophthalmological data plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 18 publications
3
26
0
3
Order By: Relevance
“…We performed a quantitative computational method for calculating the area of the fractures and the walls. 16,17 Stacks of 2mm slices were made in the coronal plane. The width of the inferior or medial orbital wall in each 2-mm-slice was measured.…”
Section: Areamentioning
confidence: 99%
“…We performed a quantitative computational method for calculating the area of the fractures and the walls. 16,17 Stacks of 2mm slices were made in the coronal plane. The width of the inferior or medial orbital wall in each 2-mm-slice was measured.…”
Section: Areamentioning
confidence: 99%
“…Avashia et al 23 developed a decision-making algorithm for orbital floor reconstruction materials by reviewing all available literature, but found no conclusive statement regarding the preferred material for orbital floor fracture repair. Other studies comparing implants also found no significant difference in outcomes between absorbable mesh plates and titanium-dynamic mesh plates, Macropore and Medpor, or (PDS) foil and titanium meshes 2 23…”
Section: Discussionmentioning
confidence: 96%
“…We performed a quantitative computational method for calculating the area of the fractures. 19,20 Stacks of 2-mm slices in the coronal plane were created. The width of the fractured orbital wall in each 2-mm slice was measured.…”
Section: Areamentioning
confidence: 99%